Endodontic sealers and post-endodontic waiting time affect the bond strength of the fiber posts - Thais Camponogara BOHRER; Patricia Eliana FONTANA; Vinícius Felipe WANDSCHER; Victor Hugo Carvalho MORARI; Rafael PILLAR; Mariana de Carlo BELLO; Luiz Felipe VALANDRO; Osvaldo Bazzan KAIZER (Universidade Estadual Paulista, 2020)
Abstract Introduction The resistance adhesive of a fiber post can be affected by several factors, such as the endodontic sealer and post-endodontic waiting time. Objective The aim of this study was to evaluate the effect of different endodontic sealers and two different post-endodontic waiting times on the bond strength of fiber posts. Material and method Seventy-two bovine teeth were endodontically treated and filled using three endodontic sealers: eugenol-based, epoxy resin-based, or mineral trioxide aggregate-based. The specimens were stored at 37°C for 24 hours or for 30 months. After the respective storage times, the root canals were prepared for luting fiber posts using RelyX U200. Push-out tests and analysis of failures were performed. The push-out data were analyzed by two-way analysis of variance to compare the effects of the endodontic sealer and with the t-test to compare the effects of post-endodontic waiting time. Result The AH Plus sealer yielded the highest bond strength values at 30 months post-endodontics (11.26 Mpa) (p < 0.05), however no had difference with Endofill sealer at the same time. Endofill and MTA Fillapex sealers did not differ significantly in their effects, irrespective of the post-endodontic waiting time. Conclusion In conclusion, the endodontic sealer used and post-endodontic waiting time affect the adhesive resistance of fiber posts. The adhesion increases significantly when the fiber post is cemented 30 months after the root canal filling, while the adhesion is reduced when cementing immediately after root canal treatment, in particular for eugenol-based endodontic sealers.